CONTROL DRIP RATE OF INTRAVENOUS FLUIDS BASED ON HEART RATE WITH A MONITORING SYSTEM USING THINGSPEAK WEBSITE - Salam, Raja Hafizh (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
Dehydration is a state of decreasing the amount of fluid in the body accompanied by increased heart rate. One of the treatments that must be done for dehydrated patients is to give infusions periodically, which must be supervised by medical personnel. However, controlling patient intravenous fluid drops in some hospitals or public health centres is still done manually. Based on this problem, a device can adjust the drip rate of intravenous fluids based on heart rate. This research made a prototype of controlling the drip rate of intravenous fluid based on heart rate using NodeMCU ESP8266 microcontroller, MAX30100 sensor for heart rate reading, optocoupler sensor for drip rate reading, and servo motor for roller clamp drive. From the test results, the system has been able to control the drip rate of infusion based on heart rate with a range of (80 – 89) bpm which has the number of infusion droplets (24 – 35) TPM and a range (90 – 99) bpm that has the number of drip infusions (36 – 47) TPM, then send the heart rate data and drip rate of the injection to the thing speak website every 15 seconds. Heart rate readings with MAX30100 sensors have an error of 2.51% and an accuracy of 97.49%. Meanwhile, the drip rate reading with the optocoupler sensor has an error of 0.83% and an accuracy of 99.17%.